The impact of Arabic (L1) on Iraqi EFL undergraduates’ use of English prepositions at Al-Hikmah University College - et. al., Saad Sameer Dhari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study was conducted to investigate the grammatical and lexical mistakes among Iraqi undergraduates within the utilization of English prepositions and to explore if those mistakes are regular and linked with the impact of main language overlap. The study endeavored to give answers through three questions, which forms of mistakes that Iraqi Students commited when practising English prepositions as their target language?; How many mistakes that emerged when employing of English prepositions via Iraqi students?; were the mistakes in the translation of the English prepositions used by some Iraqi Students regular and associated with the primary language overlap?. The study’s sample comprised of fifty Iraqi undergraduates concerning genders in the department of Islamic Studies at Al-Hikmah Univercity College. The researcher employed a written tool called Translation test to answer the three research questions then the Data were gathered utilizing translation approach to analyse the linguistic and grammatical mistakes once practising the English prepositions through Iraqi EFL undergraduate at Al-Hikmah Univercity College as a mandatory primary question within this study. The study outcomes revealed that there was a significant variations in participants' ability to translate prepositional English phrases into Arabic after some tests. Even though there have been slightly larger shifts in data outcomes over the course of experimental training, especially in place prepositions as well as time prepositions. In terms of related systemic neuronal outputs, all those findings suggested variability across respondents.